TURNER, STEPHEN. UNDERSTANDING THE TACIT. NEW YORK: ROUTLEDGE, 2014. - Masson Maroldi, Marcelo (Pensando - Revista de Filosofia, 2015)
Review of the book: Turner, Stephen. Understanding the tacit. New York: Routledge, 2014.